Vitamin D levels and risk of ocular disorders: insights from bidirectional and multivariable Mendelian randomization analysis - Fan, Shipei; Shi, Xing-yu; Li, Xia; Li, Jun; Yu, Song-ping (Frontiers in Medicine, 2024)
This study aimed to assess the causal relationships between vitamin D levels and ocular disorders.Methods: Independent genetic variables were obtained from genome-wide association studies (GWAS) and publicly available databases. The summary statistics for 25-hydroxyvitamin D (25(OH)D) were obtained from two large-scale GWAS studies, with sample sizes of 324,105 and 417,580 European individuals. The genetic variants of myopia, primary open angle glaucoma (POAG), anterior iridocyclitis, senile cataract, diabetic retinopathy (DR), retinal vein occlusion (RVO), wet age-related macular degeneration (WAMD) and optic neuritis were extracted from the latest release of FinnGen consortium, which contains genome data from Finnish participants. Subsquently, mendelian randomization (MR) analyses were conducted to obtain effect estimates. Additionally, we performed multivariable MR analysis and mediation analysis to validate the results.Results: In the discovery dataset, genetically predicted vitamin D concentration was found to be causally associated with an increased risk of WAMD, (odd ratio (OR) = 1.35, 95% confidence interval (CI) = 1.09-1.67, PIVW = 0.005). However, no causal effects of genetically predisposed vitamin D levels on the risk of most types of ocular disorders were observed. Reverse MR revealed no causal relationships between the ocular diseases and vitamin D concentrations. The MR analyses of the validation dataset yielded consistent results. Additionally, the causal effect of vitamin D levels on the risk of WAMD remained significant after adjusting for potential confounders in the multivariable MR analysis (OR = 1.78, 95% CI = 1.19-2.66, PIVW = 0.005).Our MR analysis results provide robust evidence of a causal relationship between genetically predicted 25(OH)D levels and an increased risk of WAMD in European population. These findings offer important insights into the management and control of ocular disorders.